MeJA inhibits fungal growth and DON toxin production by interfering with the cAMP-PKA signaling pathway in the wheat scab fungus Fusarium graminearum - Kaili Duan; Shaozhe Qin; Fangling Cui; Liangyuan Zhao; Yongqing Huang; Jin-Rong Xu; Guanghui Wang (mBio, 2025)
ABSTRACT Deoxynivalenol (DON), a mycotoxin primarily produced by Fusarium species, is commonly found in cereal grains and poses risks to human and animal health, as well as global grain trade. This study demonstrates that methyl jasmonate (MeJA), a natural plant hormone, inhibits the growth and conidiation of Fusarium graminearum. Importantly, MeJA significantly reduces DON production by suppressing TRI gene expression and toxisome formation. To explore the molecular mechanism, we identified MeJA-tolerant mutants, including a transcription factor MRT1 and cAMP-PKA pathway-related genes (FgGPA1 and FgSNT1). MeJA treatment reduced PKA activity and intracellular cAMP levels in F. graminearum, suggesting it targets the cAMP-PKA pathway. Notably, the MeJA-resistant mutant FgGPA1R178H enhanced fungal growth, DON production, and cAMP levels in the presence of MeJA. Exogenous cAMP alleviated MeJA’s inhibitory effects on DON production, further supporting this pathway’s involvement. Interestingly, MeJA had no effect on all three MAP kinase pathways (Mgv1, Gpmk1, and FgHog1). Truncated and phospho-mimicking mutations in Mrt1 or FgSnt1 conferred MeJA resistance, suggesting they may act downstream of the cAMP-PKA pathway. In conclusion, MeJA presents a promising approach to control F. graminearum growth and DON production.IMPORTANCEDeoxynivalenol (DON) poses significant risks to both human and animal health and severely disrupts the global grain trade due to its prevalence as a common contaminant in wheat grains. With rising public concern over food safety, finding effective and sustainable methods to reduce DON contamination becomes increasingly urgent. In our study, we found that methyl jasmonate (MeJA), a natural plant hormone, can effectively inhibit the vegetative growth of F. graminearum and significantly reduce its DON toxin production. To explore the underlying molecular mechanism, we identified the mutations in MeJA-tolerant mutants and revealed that MeJA effectively exerts its antifungal activities by inhibiting the cAMP-PKA signaling pathway in F. graminearum. Our work provides a promising natural solution to reduce DON toxin contamination in cereal grains, enhancing food safety while decreasing the reliance on chemical fungicides and their associated environmental impact.